Find $x$ from the following equation:
1.$coesc\left( {\dfrac{\pi }{2} + \theta } \right) + x\cos \theta \cot \left( {\dfrac{\pi }{2} + \theta } \right) = \sin \left( {\dfrac{\pi }{2} + \theta } \right)$
2.$x\cot \left( {\dfrac{\pi }{2} + \theta } \right) + \sin \theta \tan \left( {\dfrac{\pi }{2} + \theta } \right) + \cos ec\left( {\dfrac{\pi }{2} + \theta } \right) = 0$
Answer
Verified
472.8k+ views
Hint: First we will convert $\left( {\dfrac{\pi }{2} + \theta } \right)$ into $\theta $ after that we will convert all the trigonometric ratio by using $\sec \theta = \dfrac{1}{{\cos \theta }}$,$\tan \theta = \dfrac{{\sin \theta }}{{\cos \theta }}$ and $\cot \theta = \dfrac{{\cos \theta }}{{\sin \theta }}$ after simplifying that equate the linear equation with 0 and find the value of $x$.
Complete step-by-step answer:
1:- Given $coesc\left( {\dfrac{\pi }{2} + \theta } \right) + x\cos \theta \cot \left( {\dfrac{\pi }{2} + \theta } \right) = \sin \left( {\dfrac{\pi }{2} + \theta } \right)$
Convert $\left( {\dfrac{\pi }{2} + \theta } \right)$into $\theta $ we get
$ \Rightarrow \sec \theta - x\cos \theta \tan \theta = \cos \theta $
We know that$\sec \theta = \dfrac{1}{{\cos \theta }}$ and $\tan \theta = \dfrac{{\sin \theta }}{{\cos \theta }}$ substituting these values, we get,
$ \Rightarrow \dfrac{1}{{\cos \theta }} - x\sin \theta = \cos \theta $
Multiplying $\cos \theta $ on both side we get,
$ \Rightarrow 1 - x\cos \theta \sin \theta = {\cos ^2}\theta $
We know that $1 - {\cos ^2}\theta = {\sin ^2}\theta $
$ \Rightarrow {\sin ^2}\theta - x\sin \theta \cos \theta = 0$
Taking $\sin \theta $ common
$ \Rightarrow \sin \theta \left( {\sin \theta - x\cos \theta } \right) = 0$
Now,
$
\Rightarrow \sin \theta - x\cos \theta = 0 \\
\therefore x = \tan \theta \\
$
2: - Given $x\cot \left( {\dfrac{\pi }{2} + \theta } \right) + \sin \theta \tan \left( {\dfrac{\pi }{2} + \theta } \right) + \cos ec\left( {\dfrac{\pi }{2} + \theta } \right) = 0$
Convert $\left( {\dfrac{\pi }{2} + \theta } \right)$ into $\theta $ we get
$ \Rightarrow - x\tan \theta - sin\theta \cot \theta + \sec \theta = 0$
We know that $\sec \theta = \dfrac{1}{{\cos \theta }}$,$\tan \theta = \dfrac{{\sin \theta }}{{\cos \theta }}$ and $\cot \theta = \dfrac{{\cos \theta }}{{\sin \theta }}$ substituting these values, we get,
$ \Rightarrow - x\dfrac{{\sin \theta }}{{\cos \theta }} - \cos \theta + \dfrac{1}{{\cos \theta }} = 0$
Multiplying $\cos \theta $on both side we get,
$ \Rightarrow 1 - x\sin \theta = {\cos ^2}\theta $
We know that $1 - {\cos ^2}\theta = {\sin ^2}\theta $
$ \Rightarrow {\sin ^2}\theta - x\sin \theta \cos \theta = 0$
Taking $\sin \theta $ common
$ \Rightarrow \sin \theta \left( {\sin \theta - x\cos \theta } \right) = 0$
Now,
$
\Rightarrow \sin \theta - x\cos \theta = 0 \\
\therefore x = \tan \theta \\
$
Note: Trigonometric formulas used in this question $coesc\left( {\dfrac{\pi }{2} + \theta } \right) = \sec \theta $,$\cot \left( {\dfrac{\pi }{2} + \theta } \right) = - \tan \theta $,$\sin \left( {\dfrac{\pi }{2} + \theta } \right) = \cos \theta $and must be taken into consideration. We can also say as $\sin \theta = 0$then $\theta = n\pi $. But in this question, we cannot consider $\theta = n\pi $because when we consider it $x = 0$which contradicts the question.
Complete step-by-step answer:
1:- Given $coesc\left( {\dfrac{\pi }{2} + \theta } \right) + x\cos \theta \cot \left( {\dfrac{\pi }{2} + \theta } \right) = \sin \left( {\dfrac{\pi }{2} + \theta } \right)$
Convert $\left( {\dfrac{\pi }{2} + \theta } \right)$into $\theta $ we get
$ \Rightarrow \sec \theta - x\cos \theta \tan \theta = \cos \theta $
We know that$\sec \theta = \dfrac{1}{{\cos \theta }}$ and $\tan \theta = \dfrac{{\sin \theta }}{{\cos \theta }}$ substituting these values, we get,
$ \Rightarrow \dfrac{1}{{\cos \theta }} - x\sin \theta = \cos \theta $
Multiplying $\cos \theta $ on both side we get,
$ \Rightarrow 1 - x\cos \theta \sin \theta = {\cos ^2}\theta $
We know that $1 - {\cos ^2}\theta = {\sin ^2}\theta $
$ \Rightarrow {\sin ^2}\theta - x\sin \theta \cos \theta = 0$
Taking $\sin \theta $ common
$ \Rightarrow \sin \theta \left( {\sin \theta - x\cos \theta } \right) = 0$
Now,
$
\Rightarrow \sin \theta - x\cos \theta = 0 \\
\therefore x = \tan \theta \\
$
2: - Given $x\cot \left( {\dfrac{\pi }{2} + \theta } \right) + \sin \theta \tan \left( {\dfrac{\pi }{2} + \theta } \right) + \cos ec\left( {\dfrac{\pi }{2} + \theta } \right) = 0$
Convert $\left( {\dfrac{\pi }{2} + \theta } \right)$ into $\theta $ we get
$ \Rightarrow - x\tan \theta - sin\theta \cot \theta + \sec \theta = 0$
We know that $\sec \theta = \dfrac{1}{{\cos \theta }}$,$\tan \theta = \dfrac{{\sin \theta }}{{\cos \theta }}$ and $\cot \theta = \dfrac{{\cos \theta }}{{\sin \theta }}$ substituting these values, we get,
$ \Rightarrow - x\dfrac{{\sin \theta }}{{\cos \theta }} - \cos \theta + \dfrac{1}{{\cos \theta }} = 0$
Multiplying $\cos \theta $on both side we get,
$ \Rightarrow 1 - x\sin \theta = {\cos ^2}\theta $
We know that $1 - {\cos ^2}\theta = {\sin ^2}\theta $
$ \Rightarrow {\sin ^2}\theta - x\sin \theta \cos \theta = 0$
Taking $\sin \theta $ common
$ \Rightarrow \sin \theta \left( {\sin \theta - x\cos \theta } \right) = 0$
Now,
$
\Rightarrow \sin \theta - x\cos \theta = 0 \\
\therefore x = \tan \theta \\
$
Note: Trigonometric formulas used in this question $coesc\left( {\dfrac{\pi }{2} + \theta } \right) = \sec \theta $,$\cot \left( {\dfrac{\pi }{2} + \theta } \right) = - \tan \theta $,$\sin \left( {\dfrac{\pi }{2} + \theta } \right) = \cos \theta $and must be taken into consideration. We can also say as $\sin \theta = 0$then $\theta = n\pi $. But in this question, we cannot consider $\theta = n\pi $because when we consider it $x = 0$which contradicts the question.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE